Craftland is Mathland: Mathematical insight and the generative role of fiber crafts in maker education - Peppler, Kylie; Keune, Anna; Thompson, Naomi; Saxena, Pooja (Frontiers in Education, 2022)
There is tremendous excitement around makerspaces for deepening and enriching curricula across subjects, as well as engaging traditionally marginalized learners in new ways. To address the underrepresentation of women in mathematics, we propose that educators aspire to create a "Mathland" when designing maker educational activities. Mathlands are environments envisioned by Seymour Papert where mathematics is learned alongside ways of doing mathematics in self-selected contexts, leading to an epistemology and natural language of mathematics that pervades all experiences. To imagine a Mathland where women’s participation in mathematics is lifelong and lifewide, we explore traditionally female-dominated fiber crafts where long-term engagement, mathematics, and heritage intersect. As part of a longitudinal embedded multi-year ethnographic study, we conducted cohort analyses as well as grounded, iterative, and thematic coding of semi-structured interview data, augmented with crafting artifacts from 65 adult fiber crafters. Using qualitative analytical techniques, we asked: How does math occur in craft? How do crafters observe the intersection between math and craft in process? Fiber crafts were found to present a “Mathland,” a lifelong context for immersive math engagement. We present crafters’ math insights in the craft, as well as multiple aspects of the crafts and surrounding communities that supported the crafters in sustaining their engagement with mathematics throughout their lifetime. This study has implications for the design of inclusive and lifelong maker educational environments for mathematics learning.